Molecular mechanism of a covalent allosteric inhibitor of SUMO E1 activating enzyme - Zongyang Lv (Nature Portfolio, 2018)
Ubiquitin and ubiquitin-like modifiers such as SUMO play important roles in several cellular pathways that can become deregulated in cancer. Here the authors describe the structural basis for inhibition of SUMO E1 ligase by the small molecule COH000.